Interconnectedness and Systemic Risk: Insights from Indonesian Financial Conglomerates - Kusumahadi, Teresia Angelia; Saadah, Siti; Permana, Fikri C (Faculty of Economic and Business, 2025)
Research Originality: This research addresses the gap in existing studies by examining the time-varying volatility spillover index among conglomerates in listed financial companies in Indonesia, an unexplored area.Research Objectives: The study investigates the potential interconnectedness among financial institutions, one source of systemic risk, by analyzing volatility spillovers within conglomerates.Research Methods: Using a generalized VAR approach, we examined total volatility spillover, directional volatility spillover, and total volatility spillover indices for 14 companies from four conglomerates, utilizing daily data from 2010 to March 2023.Empirical Results: The results reveal significant interconnectedness within these conglomerates, indicating potential for systemic risk that could threaten the financial system's stability. Another noteworthy finding is that the volatility transmission within banking conglomerates predominantly originates from subsidiary companies to parent companies.Implications: Regulators need to supervise spillovers at both the parent and subsidiary levels by developing regulations that address both levels to ensure effective risk management.JEL Classification: C58, G21How to Cite:Kusumahadi, T. A., Saadah, S., Permana, F. C. (2025). Interconnectedness and Systemic Risk: Insights from Indonesian Financial Conglomerates. Etikonomi, 24(1), 53 – 68. https://doi.org/10.15408/etk.v24i1.38452.